Redundancies in linear GP, canonical transformation, and its exploitation: A demonstration on image feature synthesis - Watchareeruetai, Ukrit; Takeuchi, Yoshinori; Matsumoto, Tetsuya; Kudo, Hiroaki; Ohnishi, Noboru (My University, 2011)
This paper concerns redundancies in representation of linear genetic programming (GP). We identify the causes of redundancies in linear GP and propose a canonical transformation that converts original linear representations into a canonical form in which structural redundancies are removed. In canonical form, we can easily verify whether two representations represent an identical program. We then discuss exploitation of the proposed canonical transformation, and demonstrate a way to improve search performance of linear GP by avoiding redundant individuals. Experiments were conducted with an image feature synthesis problem. Firstly, we have verified that there are really a lot of redundancies in conventional linear GP. We then investigate the effect of avoiding redundant individuals. The results yield that linear GP with avoidance of redundant individuals obviously outperforms conventional linear GP. © 2010 Springer Science+Business Media, LLC.
Keywords: Canonical form; Canonical transformation; Feature extraction; Linear genetic programming; Redundant representation